Muon metrology and positioning: the POMME experiment. (8th July 2021) - Procureur, S.; Attié, D.; Gomez, H.; Lehuraux, M.; Magnier, P.; Mandjavidze, I.; Mas, P.
Abstract: A muon metrology experiment is presented: two distant muon detection systems are used in coincidence to detect these particles originating from primary cosmic rays. The excellent spatial resolution of the Micromegas detectors allows for a precise relative positioning of the two instruments. The current setup can be used to monitor mid- or long-term deformations of a structure down to sub-millimeter resolution. It could also be employed to roughly position a distant structure with single muon detection, a typical example being an underground cavity whose position with respect to the surface is poorly known.